Antibacterial Activity of Ethyl Asetate Fraction of Centella asiatica Against Clinical Isolates of Pseudomonas aeruginosa - Nazilinly, Fitri; Permatasari , Lina; Hasbi, Nurmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Pseudomonas aeruginosa is one of the major worldwide medical conditions causing nosocomial contaminations with high mortality and grimness. P. aeruginosa infection treatment, on the other hand, has become more difficult due to antibiotic resistance. Therefore, new antibacterial agents are needed that can be an option in controlling and managing cases of bacterial infections. Plants that could potentially become a new antimicrobial agent is pegagan herb (Centella asiatica). This study aims to determine the antibacterial activity of ethyl acetate fraction of pegagan herb against clinical isolates of P. aeruginosa and its phytochemical profile. Pegagan herb powder was extracted with 96% ethanol, then fractionated using liquid-liquid extraction method with n-hexane, chloroform and ethyl acetate solvents. Ethyl acetate fraction of pegagan herb with 3 treatment groups of 5,000 ppm, 7,500 ppm, and 10,000 ppm were tested for antibacterial activity using disc diffusion method. The positive and negative control groups used Colistin and DMSO 10%. The results showed that all concentrations produced different inhibition zones against the growth of P. aeruginosa. Based on the mean diameter of inhibition, the concentration series of 7,500 ppm showed the most effective results with a mean of 2.69 mm compared to the other concentrations. Ethyl acetate fraction of pegagan herb contains flavonoid, phenolic and tannin compounds. Ethyl acetate fraction of pegagan herb can inhibit the growth of clinical isolates of P. aeruginosa in the weak category with inhibition zone diameter <5 mm.